Water‐Soluble Naked Gold Nanoclusters Are Not Luminescent. Issue 34 (15th May 2017) - Londoño‐Larrea, Pablo; Vanegas, Julie P.; Cuaran‐Acosta, Daniel; Zaballos‐García, Elena; Pérez‐Prieto, Julia
Abstract: Here, the synthesis of water‐dispersible naked gold nanoclusters (AuNCnaked ) is reported by a simple reduction of HAuCl4 with NaOH at room temperature, and it is shown that they are non‐luminescent. They are then easily passivated with different thiols and adenosine monophosphate, leading to luminescent NCs. This is an important finding because the photoluminescence of the passivated NCs can now be clearly attributed to the ligand–AuNC surface interaction. These results are also highly relevant from the point of view of the preparation of luminescent NCs from the same NC batch. This strategy can be valuable for the preparation of a broad range of nano(bio)composites. Abstract : Water‐dispersible naked gold nanoclusters (NCs) can be easily prepared by a simple reduction of HAuCl4 with NaOH at room temperature and they are non‐luminescent. They can then easily be passivated with different thiols and adenosine monophosphate, leading to luminescent NCs. This is an important finding because the photoluminescence of the passivated NCs can be now clearly attributed to the ligand–AuNC surface interaction.